A Study on the Oil Price Cointegration Dynamic Process: Evidence From the Shanghai Crude Oil Futures - Wang, Hongxia; Qiu, Shushu; Yick, Ho Yin; Dai, Yuhu (Frontiers in Environmental Science, 2022)
This work studies the pricing efficiency of the Shanghai crude oil futures market in terms of cointegration and Granger causality. Using the representative samples of several futures contracts covering different listing periods, we find a significant and gradual change of the relations among the Shanghai crude oil futures prices and international (West Texas Intermediate and Brent) benchmarks, from unidirectional Granger causality to bidirectional Granger causality. Moreover, the Shanghai crude oil futures market plays a leading role on domestic (Daqing) crude oil spot market. The relations become stable after about one year’s market development. Our evidence supports that it has the increasing influence on domestic crude oil market and international benchmarks.